Breakdown process and fragmentation characteristics of anthracite subjected to high-voltage electrical pulses treatment. (1st September 2020) - Yan, Fazhi; Xu, Jiang; Peng, Shoujian; Zou, Quanle; Zhou, Bin; Long, Kun; Zhao, Zhiguo
Highlights: Anthracite primarily experiences thermal breakdown and electrical breakdown stages. Porosity growth rate of seepage pores is higher than that of adsorbed pores. The larger the breakdown voltage, the more the tensile microscopic cracks. Abstract: Enhanced coalbed methane recovery using high-voltage electrical pulses (HVEP) has been a popular research topic in recent years. However, the breakdown process and fragmentation characteristics of anthracite subjected to HVEP treatment remain unclear. This limits the popularization and application of this technology. In this work, Guizhou anthracite samples were subjected to electrical pulse tests with different breakdown voltages. This was performed using a high-frequency oscilloscope to obtain the voltage and current waveforms during coal breakdown. Furthermore, the pore structure and evolution of the microscopic cracks in the coal were analyzed via field emission-scanning electron microscopy, nuclear magnetic resonance, and X-ray computed tomography. Our results reveal that the breakdown of anthracite by the electrical pulse occurs mainly in two stages: thermal breakdown and electrical breakdown. Most of the energy stored in the capacitor is injected into the plasma channel of the coal in the electrical breakdown stage, during which the coal body displays apparent damage. Additional mesopores and macropores are produced as the breakdown voltage increases. The growth rate of seepage pores is significantly higher than that of adsorbed pores under a fixed breakdown voltage. In addition, the seepage pores of coal samples after HVEP treatment exhibit significant fractal characteristics. Meanwhile, several radial tensile microscopic cracks are formed inside the coal body. In general, the larger is the breakdown voltage, the more abundant are the tensile microscopic cracks. The mineral impurities in a coal body affect the expansion of the discharge channel. This, in turn, affects the direction of microscopic crack expansion.